The Effect of TikTok Live Shopping on Consumer Behavior in Surabaya Fashion Industry - Shafani Anataya Prasetyo, Cheerisa; Hartono, Wendra (Journal of Accounting and Finance Management, 2025)
The rapid growth of TikTok Live Shopping has transformed consumer behavior in Indonesia’s fashion industry, particularly among young urban audiences. This study aims to examine the influence of interactive features, discount promotions, and fear of missing out (FOMO) on impulsive buying behavior in the Surabaya fashion market. Guided by the Stimulus–Organism–Response (SOR) framework, the research employs a quantitative approach with purposive sampling, targeting 384 respondents aged 18–28 who have shopping experience via TikTok Live. Data were collected through structured questionnaires and analyzed using multiple regression with SPSS. The findings demonstrate that all three independent variables: interactive features, discount promotions, and FOMO have a positive and significant effect on impulsive buying, with FOMO emerging as the most dominant factor. The simultaneous test further confirms that these predictors collectively exert a strong influence, explaining a substantial proportion of the variance in impulsive buying behavior. These results highlight the critical role of psychological triggers and interactive digital features in shaping consumer decision-making within livestream shopping contexts. The study contributes to the growing body of literature on digital commerce by emphasizing how emotional and technological drivers intersect to accelerate fashion consumption among Generation Z. Practically, the findings offer strategic insights for fashion retailers and marketers to design more engaging, urgency-driven, and socially interactive campaigns that foster consumer engagement and drive sales in competitive online marketplaces.